Effectiveness and Efficiency of Regional Budget Performance: Evidence from North Barito Regency (2020–2024) - Renny Indah Purnama Sari; Sunaryo N. Tuah; Benius (Institut Bisnis dan Informatika Kesatuan, 2025)
This study analyzes the effectiveness and efficiency of the implementation of the regional revenue and expenditure budget in North Barito Regency from 2020 to 2024. Using a descriptive quantitative approach and longitudinal analysis, the research evaluates fiscal performance based on key indicators: revenue realization, expenditure absorption, and budget composition. The findings reveal that the average effectiveness ratio of locally generated revenue reached 98.26%, indicating strong performance and surpassing targets in 2024. Meanwhile, the efficiency ratio of regional expenditure remained consistently above 99%, reflecting disciplined budget execution. However, the composition of spending was dominated by operational expenditures, particularly personnel costs, which accounted for over 40% of total spending. Capital expenditure fluctuated and peaked in 2023 yet remained below optimal levels for long-term development impact. The study identifies persistent fiscal deficits each year, offset by increasing net financing, with the highest budget financing surplus recorded in 2024. These trends suggest both potential efficiency and weaknesses in planning and absorption. The research concludes that while regional revenue and expenditure budget implementation in North Barito is relatively effective and efficient, structural challenges remain.